The Resources Of Good Supervision - Kaarina Määttä; Satu Uusiautti (European Scientific Journal, ESJ, 2016)
A doctoral thesis is a doctoral student’s huge accomplishment, but hardly can be completed without a supervisor’s help and guidance. It is a common fact that a doctoral thesis requires abundant work from the doctorate, but not all are aware of that the supervision of doctoral theses presents a world filled with concerns and doubt as well as effort and successes. A supervisor’s joy consists of many other feelings too: relief, when a doctoral student hands his or her newly printed doctoral thesis with beautiful binding or when the auditorium doors are closed after a successful dissertation. In order to achieve the favoring review statements, a supervisor and a doctorate have to work hard for years. What kinds of resources are needed from a supervisor’s point of view? What kinds of obstacles and accelerators does a supervisor confront during the process? What makes a supervisor supervise persistently and empathetically? What are the elements of good supervision? These questions are relevant in the process of supervising doctoral theses.